Layer-by-layer coated calcium carbonate nanoparticles for targeting breast cancer cells - Bastos, F. R. (2023)
Breast cancer is resistant to conventional treatments due to the specific tumour microenvironment, the associated acidic pH and the overexpression of receptors that enhance cells tumorigenicity. Herein, we optimized the synthesis of acidic resorbable calcium carbonate (CaCO3) nanoparticles and the encapsulation of a low molecular weight model molecule (Rhodamine). The addition of ethylene glycol during the synthetic process resulted in a particle size decrease: we obtained homogeneous CaCO3 particles with an average size of 564 nm. Their negative charge enabled the assembly of layer-by-layer (LbL) coatings with surface-exposed hyaluronic acid (HA), a ligand of tumour-associated receptor CD44. The coating decreased Rhodamine release by two-fold compared to uncoated nanoparticles. We demonstrated the effect of nanoparticles on two breast cancer cell lines with different aggressiveness â SK-BR-3 and the more aggressive MDA-MB-231 â and compared them with the normal breast cell line MCF10A. CaCO3 nanoparticles (coated and uncoated) significantly decreased the metabolic activity of the breast cancer cells. The interactions between LbL-coated nanoparticles and cells depended on HA expression on the cell surface: more particles were observed on the surface of MDA-MB-231 cells, which had the thickest endogenous HA coating. We concluded that CaCO3 nanoparticles are potential candidates to carry low molecular weight chemotherapeutics and deliver them to aggressive breast cancer sites with an HA-abundant pericellular matrix.Â